Poetyckie formy pamięci o Czerwcu ’56 - Dabert, Dobrochna (Poznańskie Studia Polonistyczne. Seria Literacka, 2017)
The article is devoted to occasional poetry related to the Poznań 1956 protests. The survery was conducted within the framework of memory studies, assuming that this type of verse is mostly involved in the literary discourse of memory, and can be treated as one of the forms of forgetting. This approach is supported by theory of collective memory, with notions proposed by Pierre Nora, Jan Assmann, Marcin Kula, Andrzej Szpociński and Michel Foucault.